EFEKTIVITAS PEMBAYARAN NON TUNAI PADA UMKM DAERAH ALIRAN SUNGAI CITARUM - Rustanto, Agung Edi; Kartini, Iis (JURNAL LENTERA BISNIS, 2019)
The rapid development of non-cash payment systems has also developed non-cash payment instruments which are alternative choices for MSMEs in the Citarum river basin to increase sales because they offer convenience to customers. MSMEs in the Citarum River Basin still need to accelerate in terms of business strategies to improve their business results. This needs to be done because buying and selling transactions with a non-cash payment system can be an efficient payment alternative as well as for transactions that can increase the effectiveness of the payment system at MSMEs. This research aims to help the community and MSMEs in the Citarum watershed to be more effective in making payment systems so that people make payments more easily and can increase sales. Non-cash payment systems are very useful for business people and the community in making payments so that MSMEs in the Citarum watershed are more advanced. The method used is the biplot and logit to determine the mapping model of the effectiveness of non-cash payments to MSMEs. The results of this study are that overall perceptions of benefits, convenience and risk from MSMEs do not significantly influence the effectiveness of non-cash payments. Between Perception of Benefits, Perception of Ease and Effectiveness has a positive correlation. Risk perception with other variables has a very low correlation.Key words: effectiveness, non-cash payment system, MSME